Relationship between red cell distribution width and heart failure - M G, Rudresh; KU, Vivek (International Journal of Medical Research and Review, 2016)
Objective: Red cell distribution width (RDW) has recently been discovered to be a novel prognostic marker in patients with heart failure. There is lack of published reports regarding relationship between RDW and Heart Failure in India. The purpose of this study is to determine whether RDW levels can be used as a prognostic marker in heart failure patients. Materials and Methods: The study was a Cross-sectional study conducted with sample size of 70 subjects with heart failure and 30 subjects without heart failure were selected for the assessment of RDW. Results: The mean RDW in patient was 15.763 ± 2.609 and in controls was 13.17± 0.75 respectively. The RDW was higher in the cases compared to controls with p value of <0.001. Of the 44 patients of HFREF, 33 had RDW> 13.6 and 11 of them had RDW ≤ 13.6. When compared this distribution of RDW in HFREF with the controls, the difference was significant with a p value of 0.001. Of the 26 patients of HFPEF, 20 had RDW > 13.6 and 6 had RDW ≤ 13.6. When compared this distribution of RDW with the control group, there was a significant difference with a p value of < 0.001. Conclusion: RDW is a readily available test and with good prognostic value even when compared with a relatively expensive NT-pro BNP measurement. It can be used as an additional marker for diagnosing heart failure.